Neuralink: Between development and neurorights (Revista Direito em Debate, 2024)
The brain chip implants produced by Elon Musk's company, Neuralink, promise to connect the human brain to computers, with various objectives, including combating cerebral palsy, blindness, and even enabling human telepathy. This equipment consists of a probe with over 3,000 electrodes, inserted directly into the patient's cerebral cortex, and promises to represent the next generation of deep brain stimulation. However, the inherent risks associated with the usability of such models need to be analyzed because, in the event of the success of the endeavor, large corporations would have unrestricted access to the brains of individuals subject to the implant. Thus, a wide range of Human Rights could be jeopardized, requiring a critical debate about the use of this type of technology in the human body. The research methodology adopted was bibliographic analysis, involving the collection and analysis of existing academic productions related to the raised issues. The conclusions reached indicate that, although there is a transformative medical and therapeutic potential from the brain implant in paralyzed individuals or those with certain diseases, an ethical and responsible standard must be considered to avoid the indiscriminate use of such technology for invading the privacy of the involved individuals, especially concerning thought interpretation, geolocation, and information security. Therefore, this complex and transformative context demands an in-depth analysis of the motivations and implications of the brain prosthesis, as new disruptive technologies are developed, now depending on the refinement of a new neuroethical standard.
Keywords: Neuralink Technology; Brain Implants; Ethical considerations in Neural Interface